Nitriding of VT1-0 titanium in low-pressure non-self-maintained glow discharge with the use of different gas mixtures - Akhmadeev Y. K.; Ivanov Yu. F. Yuriy Fedorovich; Koval N. N. Nikolay Nikolaevich; Lopatin I. V.; Shchanin P. M. (2008, 2008)
Title screen